5-HT7 Receptors Regulate Excitatory-Inhibitory Balance in Mouse Spinal Cord Dorsal Horn - Comitato, Antonella; Lacivita, Enza; Leopoldo, Marcello; Bardoni, Rita (Frontiers in Molecular Neuroscience, 2022)
Serotonergic receptors of the 5-HT7 type (5-HT7Rs) are widely expressed in the central nervous system (CNS), where they modulate several functions, such as pain. Behavioral experiments in vivo have shown both anti- and pro-nociceptive actions of 5-HT7Rs, although an analgesic effect seems to be prevalent. In the spinal cord dorsal horn, the mechanisms involved in 5-HT7R-mediated synaptic modulation are still poorly understood, especially those regarding the control of synaptic inhibition. The present study investigated the modulation exerted by 5-HT7Rs on dorsal horn excitatory and inhibitory synaptic circuits, by performing patch-clamp recordings from lamina II neurons in mouse spinal cord slices. Our results show that applying the selective 5-HT7 agonist LP-211 facilitates glutamatergic release by enhancing the frequency of spontaneous postsynaptic currents (sEPSCs) and increasing the peak amplitude of excitatory postsynaptic currents (EPSCs) evoked by dorsal root stimulation. The effects on sEPSCs were still observed in the presence of the 5-HT1A antagonist WAY-100635, while the 5-HT7 antagonist SB-269970 blocked them. LP-211 was also able to increase the release of gamma-aminobutyric acid (GABA) and glycine, as shown by the increase of spontaneous inhibitory currents (sIPSC) frequency and evoked inhibitory postsynaptic currents (IPSC) amplitude. LP-211 was proved to be more effective in potentiating synaptic inhibition as compared to excitation: consistently, 5-HT7R activation significantly enhanced the excitability of tonic firing neurons, mainly corresponding to inhibitory interneurons. Our data bring new insights into the mechanisms of synaptic modulation mediated by 5-HT7Rs in the dorsal horn. Stronger impact on synaptic inhibition supports the hypothesis that these receptors may play an anti-nociceptive role in the spinal cord of naïve animals.